2011
DOI: 10.1177/1362361311416830
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, wellbeing and parental self-efficacy in mothers of children with an Autism Spectrum Disorder

Abstract: Raising a child with an Autism Spectrum Disorder (ASD) presents significant challenges for parents that potentially have a impact on their health and wellbeing. The current study examined the extent to which parents experience fatigue and its relationship to other aspects of wellbeing and parenting. Fifty mothers of children with an ASD aged 2-5 years participated in the study. Compared with mothers of typically developing children, mothers of children with an ASD reported significantly higher fatigue, with ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
135
1
17

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(169 citation statements)
references
References 40 publications
16
135
1
17
Order By: Relevance
“…Replicating a finding by Giallo et al (2011), parenting selfefficacy was negatively associated with parenting stress, suggesting that parents who feel less confidence in their abilities feel more overwhelmed by the many demands of raising a child with an ASD. In addition, there was an inverse correlation between parenting selfefficacy and family chaos, a relationship that warrants further analysis.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Replicating a finding by Giallo et al (2011), parenting selfefficacy was negatively associated with parenting stress, suggesting that parents who feel less confidence in their abilities feel more overwhelmed by the many demands of raising a child with an ASD. In addition, there was an inverse correlation between parenting selfefficacy and family chaos, a relationship that warrants further analysis.…”
mentioning
confidence: 55%
“…Additionally, parents of children with ASD demonstrate decreased confidence in their parenting abilities. This decrease in parenting self-efficacy (PSE) is important to assess given the association between low PSE and increased levels of parenting stress in parents of children with disabilities (Giallo et al 2011). Sofronoff and Farbotko (2002) noted that increased PSE postintervention was associated with fewer reported child behavior problems, suggesting that increases in PSE provides a direct benefit to the child with ASD.…”
Section: Impact Of Asd On Parents and Familiesmentioning
confidence: 99%
“…Those studies and another one conducted in Australia (17) show that a large part of the participants quit working to stay at home and take care of the child with ASD. It was also observed in the participants of G1 and G2 of this research, where 55% of the children's caretakers reported to be house wives, without any paid employment or day-job.…”
Section: Discussionmentioning
confidence: 99%
“…Further, delinquent behavior and emotional distress in children are directly related to the presence of stressors among caregivers [28,29], which may contribute to negative behavior between caregivers [30,31]. There is a positive correlation between difficult childhood behavior and caregiver frustration and dissatisfaction [28,32]. Developmental disability in a child can also have a significant impact on caregiver stress [33,34], often resulting in severe complications in the caregivers' primary relationship [35,36].…”
Section: Instrumentsmentioning
confidence: 99%